Crecimiento Y Partición De Biomasa De Dos Cultivares De Maní (Arachis hypogaea L.) En Distintas Fechas De Siembra En Río Cuarto, Córdoba (Argentina) - Morla, Federico D.; Giayetto, Oscar; Cerioni, Guillermo A.; Fernandez, Elena M. (European Scientific Journal, ESJ, 2016)
Crop management practices like the choice of sowing date and of the cultivar modify and affect the environmental conditions of radiation and temperature in which peanut crop grows and develops. The aim of this study was to evaluate the effect that three contrasting sowing dates (SD) had on the growth and partition of biomass of two peanut cultivars of different cycle length; in the peanut-region of Rio Cuarto, Córdoba (Argentina). The experiment was conducted under field circumstances, without restrictions in water, nutrition or sanitary conditions during 2009/10 and 2010/11 growing season in the experimental field of the FAV-UNRC. On a Typical Haplustol soil with a clear light sandy texture. The Granoleico cultivars (runner type with cycle> 155 days) and Utre cultivars (cross runner x Spanish cycle of 130-140 days) were sown in early October, November and December (1st, 2nd and 3rd SD, respectively). During the growth cycle, environmental conditions were recorded, ecophysiological variables of development (phenology, thermal date) and growth (radiation interception, crop growth rate, biomass partitioning factor) of the crop were determined. At harvest, the yield components and market quality were determined, and the conditions to which the crop was exposed were analyzed. The phenological stages of peanut occurred in different environmental regimen due to variations in cycle length of the cultivars, sowing dates and the interaction between these variables. During the early SD, the duration of the cycle was longer, obtaining a greater amount of radiation as compared to the other SD. Both parameters, duration of the cycle and intercepted radiation (IPAR), decreased with late sowing. By delaying the SD, the crop growth rate (CGR) is greater during the initial periods of the crop cycle; an anticipation in the moment of maximum CGR can be seen, changes that occur in response to increased temperature and incident radiation (PAR), reflected in the pattern of biomass production and partition to the different plant organs. The combination of the SD and the length cycle of the cultivars affected the location of the critical period of definition of the yield components and the amount of radiation obtained by the crop. Particularly, the weight of ripe pod and grains was affected, which decreased by delaying the SD, with similar behavior in both cultivars and years of study. As a result, the pod yield and market quality is reduced with the delay of sowing date in both cultivars.